2012
DOI: 10.1161/circulationaha.112.104786
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Adult Congenital Heart Disease

Abstract: Background-Sudden cardiac death (SCD) is a major cause of mortality in adults with congenital heart disease (CHD).The aim of this study was to determine the adult CHD population at risk of SCD and the clinical parameters associated with SCD. Methods and Results-We performed a multicenter case-control study. Patients who died suddenly as a result of proven or presumed arrhythmia were included (cases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(195 citation statements)
references
References 35 publications
4
181
2
8
Order By: Relevance
“…Wiążą się one z niewydolnością serca, omdleniami, incydentami zakrzepowo-zatorowymi oraz nagłymi zgonami www.kardiologiapolska.pl [963][964][965][966][967]. Substrat patofizjologiczny jest złożony i związa-ny z przerostem, włóknieniem, hipoksemią, przewlekłym przeciążeniem hemodynamicznym oraz bliznami i łatami chirurgicznymi.…”
Section: Tachyarytmie Przedsionkoweunclassified
“…Wiążą się one z niewydolnością serca, omdleniami, incydentami zakrzepowo-zatorowymi oraz nagłymi zgonami www.kardiologiapolska.pl [963][964][965][966][967]. Substrat patofizjologiczny jest złożony i związa-ny z przerostem, włóknieniem, hipoksemią, przewlekłym przeciążeniem hemodynamicznym oraz bliznami i łatami chirurgicznymi.…”
Section: Tachyarytmie Przedsionkoweunclassified
“…In the analyzed subjects who have been affected with the disease since birth, it is rather the severity of a given defect that worsens a patient's prognosis. Also the fact of undergoing potentially beneficial cardio--surgery turned out to have no prognostic value, as repairs are usually performed in advanced cardiac anomalies and remaining scars may be the origin of arrhythmia [1][2][3][4][5]. Our study showed in turn the predominance of males among MTWA (non-) patients with male gender being also a factor that increases the probability of this phenomenon.…”
Section: Discussionmentioning
confidence: 77%
“…Sudden cardiac death (SCD), mostly resulting from ventricular arrhythmia, remains a cause of mortality in 19-30% of adults with congenital heart defects [1][2][3][4][5]. Such dramatic events in this relatively young population prompt to investigate indications for implantable cardioverter-defibrillator (ICD) therapy in primary prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the researchers' endeavour to improve early risk stratification, it is yet unknown whether it leads to improved outcomes in the targeted patient population. Several clinical values associated with SCD in rTOF patients are similar to the risk factors for SCD in patients with ischemic and dilated cardiomyopathy: supraventricular tachycar- dia (SVT), increased QRS (≥180 ms) duration, prolonged QT dispersion, left ventricular systolic dysfunction [18].…”
Section: Sudden Cardiac Deathmentioning
confidence: 90%